Edukasi Penatalaksanaan Penyakit dan Pengelolaan Obat Secara Mandiri pada Era New Normal di Yayasan Pendidikan Dria Raba - Herleeyana Meriyani; Dwi Arymbhi Sanjaya; Rr. Asih Juanita; Nyoman Budiartha Siada (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Corona Virus Disease (Covid-19), which was declared as pandemic by the World Health Organization in March 2020, had a major impact on the entire world population, including people with disabilities. The aims of this activity were to provide information about the self-disease management of several diseases for blind people in the new normal era and provide information to caregivers at the Yayasan Pendidikan Dria Raba Bali regarding the management of medicines storage. This action was conduct-using audiobook for people with visual disabilities and banners for caregivers at the Yayasan Pendidikan Dria Raba. To measure the effectiveness of these activities was comparing pre-test and post-test score statistically with a 95% confidence level. This action was attended by 28 participant consist of 24 blind people and 4 caregivers. The results showed a significant increase between the pre-test and post-test scores of educational blind participants from 65 to 85 (p<0.05). The results showed a significant increase in the pre-test and post-test caregiver’s score from 74 to 91 (p<0.05). The education increase the knowledge of blind people and caregivers at the Dria Raba Education Foundation. Furthermore, other audiobook with various health topics for instance infection control needs to be created to improve the health quality of blind people.